Implication of Humor in Human Conversations - Kristina Gultom; Suci Chairunnisa; Risma Sari; Ega Sauly Sitio (JELITA, 2020)
Pragmatics can be defined as a branch of linguistics that studies deiksis, presupposition, discourse analysis and conversational implicature. Implicature can be interpreted as a hidden intention behind the speech. Meanwhile, conversational implicatures are only known by most people who know the context tuturannya alone. Conversational implicatures are trying to analyze a conversation in order to obtain the correct meaning. Humour is the mental ability to discover, express or appreciate something funny or something really unusual. Funny is an adjective that means making people laugh out loud or through absurdity, strangeness, something excessive or real eccentricity.